GENDER ISSUES IN PUBLIC SPACES WITHIN MUSLIM COMMUNITIES: A SYSTEMATIC LITERATURE REVIEW - Hafith, Abdul; Nikmatullah; Dahlia Hidayati (Multidisciplinary Indonesian Center Journal (MICJO), 2025)
Gender issues in public spaces and Muslim communities have increasingly gained attention in academic discourse due to their strong connection with social norms, cultural values, and religious interpretations that shape women's patterns of participation. This study aims to examine the influence of gender norms and values within Muslim communities on women’s engagement in public spaces, uncover the challenges they face, and formulate recommendations based on feminist and social constructionist perspectives to promote gender equality. The research employs a Systematic Literature Review (SLR) method by tracing reputable academic databases through rigorous selection and thematic analysis. The findings reveal that Muslim women’s participation in public spaces is often hindered by patriarchal constructions, discrimination, and limited access. Nevertheless, women have developed strategies of resistance and negotiation that expand their roles. Thematic analysis identifies three main patterns: women’s representation in public spaces, gender-based social practices that impose limitations, and resistance strategies through religious reinterpretation and community activism. This article contributes to theoretical development by enriching global feminist perspectives through the lived experiences of Muslim women while also offering practical contributions in the form of inclusive and socially–religiously sensitive public policy recommendations. The implications highlight the importance of cross-cultural studies and the exploration of women’s experiences at the local community level to broaden understanding of gender equality in contemporary Muslim societies.